Association of sexual relationship power with PrEP persistence and other sexual health outcomes among adolescent and young women in Kenya and South Africa - Rousseau, Elzette; Wu, Linxuan; Heffron, Renee; Baeten, Jared M.; Celum, Connie L.; Travill, Danielle; Delany-Moretlwe, Sinead; Bekker, Linda-Gail; Bukusi, Elizabeth; Omollo, Victor; van der Straten, Ariane; O’Malley, Gabrielle; et al. (Frontiers in Reproductive Health, 2023)
Introduction Gendered power inequalities impact adolescent girls’ and young women's (AGYW) sexual and reproductive health (SRH) outcomes. We investigated the influence of sexual relationship power on AGYW's SRH outcomes, including HIV pre-exposure prophylaxis (PrEP) persistence. Methods The POWER study in Kisumu, Kenya, and Cape Town and Johannesburg, South Africa provided PrEP to 2,550 AGYW (aged 16–25). AGYW's perceived power in their primary sexual relationship was measured among the first 596 participants enrolled using the Sexual Relationship Power Scale's (SRPS) relationship control sub-scale. Multivariable regression was used to test for (1) key sociodemographic and relationship characteristics associated with relationship power; and (2) the association of relationship power with SRH outcomes including PrEP persistence. Results In this cohort, the mean SRPS score was 2.56 (0.49), 542 (90.9%) initiated PrEP; 192 (35.4%) persisted with PrEP at 1 month of which 46 (24.0% of 192) persisted at 6 months. SRPS were significantly lower among AGYW who cohabited with their sex partner (−0.14, 95% CI: −0.24 to −0.04, p = 0.01), or had ≥1 sex partner (−0.10, 95% CI: −0.19 to −0.00, p = 0.05). AGYW with lower SRPS were more likely to not know their partner's HIV status (aOR 2.05, 95% CI: 1.27 to 3.33, p < 0.01), but SRPS was not associated with PrEP persistence, STI infection, condom, or hormonal contraception use. Discussion AGYW's reasons for initiating PrEP and reasons for continuously using PrEP may be different. While low relationship power was associated with perceived HIV vulnerability, AGYW's PrEP persistence may be influenced by more than relationship power.